SEGMENTASI PASAR BUAH JERUK KEPROK LOKAL (Citrus Nobilis L) DI KOTA MALANG - Jatmiko Setiaji; Karunia Setyowati Suroto (Universitas Tribhuwana Tunggadewi, 2022)
Citrus fruit is one of the most popular types of fruit by people in Indonesia, citrus fruit is a fruit that is always available throughout the year because citrus plants do not know a special flowering season. The purpose of this study was to determine the market segmentation of local tangerines in Malang City based on a SWOT analysis. The determination of the area is carried out purposively or intentionally at the Blimbing Market, Malang City, based on the consideration that this area is an area that has various marketing locations, ranging from traditional markets to modern markets (supermarkets) and between the two marketing places there is no very significant quantitative difference. The method of collecting data is utilizing interviews, questionnaires, or questionnaires and observations, while the data analysis method used is descriptive quantitative-qualitative SWOT analysis. The result showed that ideal market segmentation after a SWOT analysis adapted to a matrix analysis of internal-external strategic factors for the marketing of local tangerines is the SO (strengths-opportunities) and WO (weaknesses - opportunities) strategies. The SO strategy is to maintain taste quality, increase production, increase supply to all fruit markets (outlets, fruit shops, traditional markets), and improve sales quality and marketing areas. The WO strategy is to improve the quality of production, improve packaging, expand market share, increase post-harvest anticipation, shorten marketing channels, and dominate market share.